The crystal structure of diaqua-bis(2-(3-(1H-pyrazol-4-yl)-1H-1,2,4-triazol-5-yl)pyridine-κ2 N:N′)-bis(3,5-dicarboxybenzoato-κ1 O)cobalt(II), C38H30CoN12O14 - Yong-Hua Zhang; Wen Meng-Yao; Yan Ke (Zeitschrift für Kristallographie - New Crystal Structures)
C38H30CoN12O14, triclinic, P1‾ $P‾{1}$ (no. 2), a = 6.9503(3) Å, b = 7.0244(4) Å, c = 20.1182(9) Å, α = 92.261(4)°, β = 95.206(4)°, γ = 104.600(4)°, V = 944.59(8) Å3, Z = 1, R gt(F) = 0.0408, wR ref(F 2) = 0.0910, T = 287 K.